Pemanfaatan Algoritma A Star dalam Menentukan Rute Wisata di Kota Palangka Raya - Sriyanto, Naufal Ihsan; Maulana, Ferdy Afriza; Aprilian, Rivan; Christian, Efrans; Pranatawijaya, Viktor Handrianus (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2024)
The Utilization of the A* Algorithm in Determining Tour Routes in Palangka Raya City is a study aimed at providing a solution for determining optimal tourist routes for visitors in Palangka Raya City. By employing the A* algorithm, this research offers an efficient tool to find the shortest route between selected tourist destinations, considering both distance and travel cost. The method involves initializing a graph that represents the relationships between tourist destinations, followed by the implementation of the A* algorithm for finding the best route. The research findings demonstrate that this algorithm can provide optimal routes with accurate estimations of distance and cost. A brief discussion on the research results highlights the strengths and limitations of this algorithm in the context of tourism applications. In conclusion, this research makes a significant contribution to facilitating visitors in planning their tourist trips in Palangka Raya City, with the potential positive impact on the tourism industry and visitor experiences.